Creating Counter-Spaces of Resistance and Sanctuaries of Learning and Teaching: An Analysis of Freedom University. Issue 7 (July 2014) - Muñoz, Susana; Espino, Michelle M.; Antrop-González, René
Background/Context: In 2011, the Georgia Board of Regents passed an educational policy that denies qualified students without documentation access to five selective institutions of higher education in the state. As a form of civil disobedience, Freedom University in Athens, Georgia, was founded to cultivate a space where students without documentation can continue their postsecondary educational pursuits. Research Questions: The research questions that guided this study are: (a) In what ways does Freedom University serve as a sanctuary of teaching and learning from the perspectives of faculty members? and (b) What challenges and successes have been and continue to be experienced by the faculty of Freedom University in developing sanctuaries of teaching and learning for students without documentation? Research Design: This qualitative case study included in-depth interviews with three founding faculty members. It also included document analysis that was based on historical aspects associated with the formation of Freedom Schools during the Civil Rights era and the concept of school as sanctuary to understand the pedagogical and philosophical underpinnings associated with the establishment of Freedom University. Through constant comparative data analysis, the authors uncover how Freedom University operates as a sanctuary for students without documentation. Findings: The findings demonstrate that Freedom University is a postsecondary sanctuary school because it centers students' experiences within the curriculum and embodies transformational resistance by both students and faculty. Conclusions/Recommendations: The authors suggest that, by creating sanctuaries at a post-secondary level, students without documentation are afforded a space to continue their education not for a college degree but for the sake of learning.